Indicadores metabólicos sanguíneos de gallinas ponedoras alimentadas con dietas de Plukenetia volubilis L. y Bactris gasispaes - Viamonte-Garcés, María Isabel (2025)
The aim of this study was to evaluate blood metabolic indicators in Hy-line Brown laying hens fed different inclusion levels of Plukenetia volubilis L. (sacha inchi) and Bactris gasipaes (peach palm) for 60 days. A completely randomized design was used with 108 45-day-old hens distributed in five treatments with three replicates each. The diets consisted of inclusion levels of 5 and 10% of chontaduro (diets I and II), 5 and 10% of sacha inchi (diets III and IV), and a control diet. Blood samples were taken from 36 randomly selected hens within each replicate. Hepatic transaminases TGP (ALAT) and TGO (ASAT), triglycerides, creatinine, total proteins, albumin, glucose, urea, cholesterol, HDL, and uric acid were determined in blood serum. Hens fed diet III (5% sacha inchi) exhibited the lowest values for glucose (155.39 mg/dl), cholesterol (176.40 mg/dl), and triglycerides (399.47 mg/dl). Blood biochemical profile levels with the use of sacha inchi and peach palm meals at 5% inclusion levels in the diet may maintain health levels in line with established standards for the studied strain.